Neurodevelopmental Outcomes in Very Low Birth Weight Infants Using Aminophylline for the Treatment of Apnea - Shu-Leei Tey; Wei-Te Lee; Pei-Lun Lee; Chu-Chong Lu; Hsiu-Lin Chen (Pediatrics and Neonatology, 2016)
Aminophylline has been widely used in the treatment of apneic episodes in premature infants. Animal models suggest caution in the use of aminophylline as it may increase the cerebral metabolic rate and decrease the rate of anoxic survival in neonates. This study aimed to evaluate the neurological outcomes in very low birth weight (VLBW) infants treated with aminophylline for apnea in our neonatal intensive care unit. Methods: All VLBW infants (body birth weight < 1500 g) admitted to our neonatal intensive care unit between January 2000 and December 2011 were enrolled in this retrospective study. Clinical characteristics and outcomes of these infants were reviewed and recorded. Scores on the Bayley Scales of Infant Development at 6 months, 12 months, and 18 months of corrected age were also recorded. The controls (who did not receive aminophylline) were matched for gestational age with the aminophylline group. Results: The baseline characteristics of the aminophylline group and the control group were similar. The neurodevelopmental outcomes as well as rates of patent ductus arteriosus, brain injury, severe retinopathy of prematurity, and necrotizing enterocolitis were not significantly different between the two groups. Only bronchopulmonary dysplasia remained significantly higher in the aminophylline group after adjusting for risk factors (48.08% vs. 21.15%; adjusted odds ratio: 12.50; p < 0.001). Conclusion: Aminophylline therapy for apnea of prematurity had no apparent and additional risk on the neurodevelopmental outcomes of VLBW infants at a corrected age of 18 months. Further studies with a larger sample size are needed to confirm the adverse neurological effects of aminophylline treatment.